KARAKTERISASI SIFAT FISIK DAN MEKANIK TANAH TIMBUNAN BABALESI YANG BERDASAR DARI LIMBAH BAUKSIT DAN BAKTERI PROBIOTIK: KARAKTERISASI SIFAT FISIK DAN MEKANIK TANAH TIMBUNAN BABALESI YANG BERDASAR DARI LIMBAH BAUKSIT DAN BAKTERI PROBIOTIK - marini, lelly; Hariyani, susi; Purnama, Ikhwan Arief (RETENSI, 2021)
Bauxite waste in the form of red mud is known as waste could pollute water and soil in theenvironment around the mining area and endanger public health if not given advance prevention. Bythe increasing amount of waste and the growing amount of bauxite production, this problem becomeimportant issue for the mining sector, the government and the surrounding public directly affected.Utilization on a large scale and environmentally friendly are the points in this bauxite waste solution.The Babalesi landfill for road construction is a consideration in utilizing bauxite waste by usingprobiotic bacteria as a modifier. The feasibility and potential testing of Babalesi soil is carried out byphysical and mechanical tests of the soil based on ASTM Standards. These tests produce parametersthat refer to the AASHTO and USCS Classifications to determine the requirements for embankment2soil. For the physical test in the initial test of the red mud condition, the parameters indicated the A-7-6 classification, namely clay with poor quality. Furthermore, the physical test on Babalesi soilshowed A-4 classification, namely silt soil with medium quality. Meanwhile, the mechanical test forboth conditions, namely the original red mud condition and the Babalesi soil condition, could not becarried out because even in dry conditions, Babalesi soil proved to be very hard, but if it was inwatery conditions as a procedure in the mechanical test, it could not be formed and the mechanicalparameters could not be measured. The results of the physical test concluded that Babalesi landfillmeet the requirements and could be recommended as a road construction embankment. Themanufacture of Babalesi soil could be carried out directly in the waste pond by layered way usingheavy equipment as a stirrer of bacterial solution and bauxite waste.